Kemampuan Pemecahan Masalah Matematika Pada Soal Open Ended Materi Lingkaran Berdasarkan Kemampuan Awal Matematika Siswa - Tri Rahayu Agustina; Sri Subarinah; Nurul Hikmah; Amrullah Amrullah (Griya Journal of Mathematics Education and Application, 2021)
The research was aims to describe the problem solving in mathematics ability on open ended with circle material based on the early mathematical ability of the students at 9th grade junior high school 8 mataram. The type of the research is a descriptive study with quantitative approach. The research subject are 28 students which selected with purposive sampling. The subject is grouped according to early abilities of high, moderate, and low mathematics using the midterms. The data-collection method used is an open-ended problem-solving test on a loop of 2 terms of description and interview methods. The results were analyzed based on an indicator of problem solving capability according to Polya. Based on the data analysis, student problem solving capabilities with advanced mathematical abilities fall into good category, averaged 79.69. The student problem-solving capability with the early math skills is in good category, with an average score of 77.50. Student problem solving with early abilities of low math falls in the less category, with an average value of 48.30. The students with advanced math skills and are filling indicators of understanding the problem, planning a settlement and carrying out a completion plan, but have not yet met the checking indicator.